Tešanj in 16th Century - Husić, Aladin (Prilozi za orijentalnu filologiju, 2017)
Due to its geostrategic positioning Tešanj has had frequent shift of titleholders in a short historical period, from Bosnian vassal king (1465-1476) to Hungarian and Ottomans. The first news of ottoman sources about Tešanj comes from that period. But its permanent occupation and entrance under the ottoman rule occurred during the reign of sultan Selim I (1512-1520) in October 1512. During the first years of ottoman rule Tešanj’s frontier positioning had conditioned its development. Since the whole area was devastated and depopulated, one of the first tasks of the new authority was populating Tešanj and the area. Majority of the first settlers in Tešanj were from around Zenica, Travnik and Visoko. Soon Tešanj overcame the difficulties and by the middle of 16th century it grew into a town that was proclaimed to be kasaba in 1559. Ferhad-beg was the most important person for the urban development of Tešanj in 16th century. He bequeathed a mosque and many other endowments in this town. By the end of 16th century Tešanj was listed among ten biggest towns of Bosnian Sanjak, with three sacral facilities, a mosque of sultan Selim, masjid Sufi Oruč and a mosque of Ferhad-beg, and many other facilities like shops, a khan, caravanserai, that contributed to the new urban image of the town. With the first reliable sources about Tešanj appeared first information about military activities. Presence of military forces was evident throughout the 16th century. Their presence and activities depended on military conditions. Thus the garrisons in Tešanj included ulufecis, timar holders, and at the end of 16th century they were funded from state treasury. Some documented economic activities display various effects. The most important was agricultural production, which was somewhat higher than expected in production of wheat, as well as in viticulture. Crafts were lower than expected, though it should be noted that in the second half of 16th century crafts were often not documented in their real range. However, Tešanj was still at the top among urban settlements in Bosnian Sanjak.